Removal of chromium(VI) from wastewater through ion exchange. Kinetic and scale up studies - Ahmad, Syed Waqas; Zafar, Muhammad Shahzad; Ahmad, Sajjad; Zia-ul-haq, M.; Ashraf, Muhammad; Rabbani, Javed; Ullah, Sami (Oficyna Wydawnicza Politechniki Wrocławskiej, 2019)
Chromium(VI) ions were removed from industrial wastewater. In this regard, a rig was fabricated carrying alkaline anion resin. Various experiments were carried out by varying pH, temperature and volumetric flow rate of solution by employing a rig to study the kinetics of the ion exchange process. The rate constant (k) and maximum solid phase concentration of exchanged solute (q0) were calculated using the Thomson equation to scale up the purification process of industrial runoff of chromium(VI) from the tanning, photography and ceramic industry. Experimental optimization revealed that developed setup will remove chromium( VI) to a level of 5 mg/dm3 from 300 mg/dm3 in 40 000 dm3 of wastewater. To achieve the best results for the flow rate of 10 000 dm3/day, 12.03 kg of anionic resin were recommended by fixing the pH of the setup at 7.4 while maintaining the treatment temperature at 20 °C.
Environment Protection Engineering. Vol. 45, 2019, nr 1, s. 17-29
Keywords: ochrona środowiska; inżynieria środowiska